2019
DOI: 10.1016/j.bbr.2019.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal empathy-like pro-social behaviour in the valproic acid model of autism spectrum disorder

Abstract: Impairments in social behaviour are a defining feature of autism spectrum disorder (ASD).Individuals with ASD also usually present some difficulty to recognise or understand another person's feelings. Therefore, it is possible that altered empathy processing could hinder typical social interaction in ASD. Recently, robust paradigms confirmed that rodents show primordial forms of empathy-like behaviour. Therefore, in this work, we used one of these new protocols to test pro-social behaviour in the rat model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…At adolescence, VPA-exposed rats display atypical patterns of social play behavior, that is the most characteristic and rewarding social activity displayed by young mammals: indeed, compared to control animals, rats prenatally exposed to VPA respond to play solicitation mainly by partial rotation and evasion, rather than reciprocating the playful interaction (Servadio et al, 2016; Melancia et al, 2018). The social deficits displayed by VPA-exposed rats are long lasting, since they also persist at adulthood (Schneider and Przewłocki, 2005; Schneider et al, 2006, 2008; Markram et al, 2008; Kim et al, 2011, 2014; Servadio et al, 2016, 2018; Hirsch et al, 2018; Melancia et al, 2018; Fontes-Dutra et al, 2019) and are evocative of the social disturbances displayed by autistic patients over the course of development.…”
Section: Introductionmentioning
confidence: 99%
“…At adolescence, VPA-exposed rats display atypical patterns of social play behavior, that is the most characteristic and rewarding social activity displayed by young mammals: indeed, compared to control animals, rats prenatally exposed to VPA respond to play solicitation mainly by partial rotation and evasion, rather than reciprocating the playful interaction (Servadio et al, 2016; Melancia et al, 2018). The social deficits displayed by VPA-exposed rats are long lasting, since they also persist at adulthood (Schneider and Przewłocki, 2005; Schneider et al, 2006, 2008; Markram et al, 2008; Kim et al, 2011, 2014; Servadio et al, 2016, 2018; Hirsch et al, 2018; Melancia et al, 2018; Fontes-Dutra et al, 2019) and are evocative of the social disturbances displayed by autistic patients over the course of development.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that when patients taking high doses of VPA, i.e., 600 mg to 900 mg, the amount of VPA in patient gastrointestinal tract may reach at the concentration of 100 µM, which may affect the fatty acid biosynthesis in gut microbiome of patients. VPA induced abnormal autism-like behaviors in mice 8 , and many studies showed the possible risk of VPA on autism spectrum disorders [9][10][11][12][13][14] . The present work demonstrated that the biosynthesis of certain fatty acids was completely inhibited by VPA, while that of some fatty acids was induced by VPA.…”
Section: Discussionmentioning
confidence: 99%
“…1 Structure elucidation of fungal metabolites by spectroscopic techniques. 1 H, 13 C, and 2D NMR spectroscopic data were obtained from on 400 MHz NMR spectrometer ( 1 H at 400 MHz, 13 C at 100 MHz), or 600 MHz NMR spectrometer ( 1 H at 600 MHz, 13 C at 150 MHz). Deuterated CDCl 3 was used as an NMR solvent.…”
Section: Methods Cultivation Of Microorganismsmentioning
confidence: 99%
“…RSV administration (at doses of 3.6 mg/kg, subcutaneously) also prevented sensory deficits assessed by nest-seeking behavior and in a whisker nuisance task [25]. However, RSV has no effects on the delayed latency to reach the nest shavings and latency to make any choice (nest or sterile shavings) in VPA-treated animals [27]. More recently, several epidemiological studies showed the possible association between ASD and maternal hormone intervention [41,42].…”
Section: Behavioral Effects Of Rsv In Animal Models Of Asdmentioning
confidence: 94%
“…For this reason, prenatal exposure to VPA in rats has been used as an approximation of ASD [23]. RSV administration (at doses of 3.6 mg/kg, subcutaneously for 12 to 13 days) prevented or reduced autistic-like social deficits in the VPA model [24][25][26] and sterotipic behaviors [27]. RSV at the same doses also prevented the reduced total reciprocal social interaction with a conspecific, the social transmission of food preference and repetitive self-grooming [26].…”
Section: Behavioral Effects Of Rsv In Animal Models Of Asdmentioning
confidence: 99%